Efficacy and Crop Response with FirstAct in ACCase-Tolerant Grain Sorghum - Randall S. Currie; Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2023)
This research was conducted to determine the efficacy of quizalofop (FirstAct) herbicide in herbicide-tolerant grain sorghum. FirstAct herbicide was evaluated for efficacy and crop response in Double Team (ACCase-tolerant) sorghum. All herbicides controlled Palmer amaranth 90% or more and volunteer corn 95% or more late in the season. Johnsongrass control was 86 to 91%. Minor sorghum injury early in the season did not persist. Sorghum receiving FirstAct late postemergence yielded more grain than the nontreated control or sorghum receiving Parallel Plus preemergence.
Keywords: Herbicide-resistance; volunteer corn; grain sorghum; johnsongrass; palmer amaranth